Brunner's Gland Adenoma–An Uncommon Cause for Intussusception and Gastric Outlet Obstruction. Issue 12 (5th December 2022) - Teh, Readon; Tee, Wei De; Chen, Weihao; Qurishi, Absar Ahmed
ABSTRACT: Brunner's gland adenoma is extremely uncommon small bowel tumors with an incidence of <0.01% and account for less than 1% of all gastrointestinal tumors. They are branched acinotubular glands found within the submucosal layer and located between the pyloric ring and the major duodenal papilla. Brunner's glands produce an alkaline secretion containing viscous mucin to protect the duodenum from acidic gastric chyme. Although these lesions are usually asymptomatic and are incidentally discovered on upper gastrointestinal endoscopy, they may occasionally present with symptoms of upper gastrointestinal hemorrhage, duodenal obstruction, and more rarely with biliary fistulation or intussusception. We present an atypical case of a large 9-cm Brunner's gland adenoma causing duodenojejunal intussusception in a 44-year-old Chinese man, who presented with long-standing epigastric pain, nausea, and vomiting.